Clinicopathological analysis of methotrexate‐associated lymphoproliferative disorders: Comparison of diffuse large B‐cell lymphoma and classical Hodgkin lymphoma types. Issue 6 (23rd May 2017) - Gion, Yuka; Iwaki, Noriko; Takata, Katsuyoshi; Takeuchi, Mai; Nishida, Keiichiro; Orita, Yorihisa; Tachibana, Tomoyasu; Yoshino, Tadashi; Sato, Yasuharu
Abstract : Patients with rheumatoid arthritis often develop methotrexate‐associated lymphoproliferative disorders (MTX‐LPD) during MTX treatment. MTX‐LPD occasionally regresses spontaneously after simply discontinuing MTX treatment. In patients without spontaneous regression, additional chemotherapy is required to avoid disease progression. However, the differences between spontaneous and non‐spontaneous regression have yet to be elucidated. To clarify the factors important for spontaneous regression, we analyzed the clinicopathological features of 51 patients with rheumatoid arthritis who developed MTX‐LPD (diffuse large B‐cell lymphoma [DLBCL]‐type [ n = 34] and classical Hodgkin lymphoma [CHL]‐type [ n = 17]). We examined the interval from MTX discontinuation to the administration of additional chemotherapy. The majority of DLBCL‐type MTX‐LPD patients (81%) exhibited remission with MTX discontinuation alone. In contrast, the majority of CHL‐type MTX‐LPD patients (76%) required additional chemotherapy. This difference was statistically significant ( P = 0.001). However, overall survival was not significantly different between DLBCL‐type and CHL‐type (91% vs 94%, respectively; P > 0.05). Thus, the morphological differences in the pathological findings of MTX‐LPD may be a factor for spontaneous or non‐spontaneous regression after discontinuation of MTX. Abstract : Many of the DLBCL‐type MTX‐LPD patients showed spontaneous remission and a better survival rate after methotrexate discontinuation. In contrast, more of the CHL‐type MTX‐LPD patients did not show spontaneous remission, and required additional chemotherapy. These findings are clinically relevant because the morphological differences in the pathological histology of MTX‐LPD might be a prognostic factor after methotrexate discontinuation.